Patient and public involvement in randomised controlled trial design and implementation: a process evaluation of the linking you to support and advice (LYSA) trial - Katarina Medved; Katie Johnston; Sasna S. Thomas; Josephine Hegarty; Gillian Casey; Roisin M. Connolly; Laia Raigal; Kate O’Connell (Research Involvement and Engagement)
Abstract Background The implementation of Patient and Public Involvement (PPI) in randomised controlled clinical trials (RCT) is crucial for improving the relevance and quality of research. PPI entails active engagement of patients and the public in various stages of the research process. The processes for effectively implementing PPI in RCTs remain underexplored and heterogeneous. Methods An explorative single case study of the Linking You to Support and Advice (LYSA) randomised controlled trial, NCT05035173, aims to evaluate the processes of implementation of PPI through different stages of the research cycle. Results The development and review of the grant application resulted in a more patient focused study development. Furthermore, the review of surveys, questionnaires and patient facing study materials led to amendments mainly referring to the language used. PPI contributors helped to co-design the symptom management resources in partnership with the project team. Evaluation of the ePRO collection tool did not result in any further amendments. PPI contributors participated in the development of the study’s acronym and focus group discussion. As a direct result of PPI input further work and research was done in the area of metastatic breast cancer. PPI contributors participated in social media work, review and co-authorship of this paper. Conclusions Implementation of PPI through different stages of RCT’s is effective. It highlighted the importance of PPI in improving the relevance and quality of research. While PPI offers numerous benefits, its implementation is not without challenges. Barriers such as resource and time constraints, and varying levels of stakeholder engagement pose a challenge to effective PPI integration.